1999
DOI: 10.1203/00006450-199903000-00022
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evidence for a Myogenic Response in the Fetal Pulmonary Circulation

Abstract: In vitro studies have suggested that pulmonary arteries can exhibit a myogenic response and that this myogenic response may be potent during the perinatal period. However, whether a myogenic response can be demonstrated to exist in vivo and the potential role of the myogenic response on the regulation of pulmonary blood flow during fetal life is unknown. We hypothesized that an acute increase in pulmonary artery pressure resulting from partial compression of the ductus arteriosus (DA) in the fetus may simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 28 publications
3
59
0
1
Order By: Relevance
“…Ductal ligation initially induces a large increase in pulmonary blood flow followed by a return to baseline flow while PA pressure remains high (1). In vivo experiments suggest that the fetal pulmonary circulation exhibits a myogenic response, where pressure-induced vasoconstriction opposes the initial increase in pulmonary blood flow following ductal ligation (43). Although the underlying mechanisms are incompletely understood, they involve impaired nitric oxide (NO) synthase (NOS)-mediated vasodilation and increased levels of reactive oxygen species (ROS) (23,43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ductal ligation initially induces a large increase in pulmonary blood flow followed by a return to baseline flow while PA pressure remains high (1). In vivo experiments suggest that the fetal pulmonary circulation exhibits a myogenic response, where pressure-induced vasoconstriction opposes the initial increase in pulmonary blood flow following ductal ligation (43). Although the underlying mechanisms are incompletely understood, they involve impaired nitric oxide (NO) synthase (NOS)-mediated vasodilation and increased levels of reactive oxygen species (ROS) (23,43).…”
mentioning
confidence: 99%
“…In vivo experiments suggest that the fetal pulmonary circulation exhibits a myogenic response, where pressure-induced vasoconstriction opposes the initial increase in pulmonary blood flow following ductal ligation (43). Although the underlying mechanisms are incompletely understood, they involve impaired nitric oxide (NO) synthase (NOS)-mediated vasodilation and increased levels of reactive oxygen species (ROS) (23,43). PPHN lambs also exhibit elevated pulmonary vascular oxidant stress relative to control lambs (7,50), and recent studies have demonstrated improved oxygenation in ventilated PPHN lambs that received intratracheal antioxidants at birth (13,49,50).…”
mentioning
confidence: 99%
“…However, the temporary pulmonary high blood flow derived from our Doppler study seemed to be more sustained compared with the one reported by Abman, in which the LPA blood flow returned to baseline value 2-3 h after the DA compression, whereas LPA pressure and resistance remained high. In an additional study by this group, the normalization of pulmonary blood flow was found to be related to myogenic response (22). We found that the surgical creation of the fistula was associated with a rapid increase of the pulmonary blood flow (in the first 30 min; n ϭ 2 fetuses) and that this high blood flow was sustained for at least 24 h. This delay in the normalization of pulmonary blood flow may reflect a less pronounced or delayed myogenic response in the fistula model.…”
Section: Discussionmentioning
confidence: 99%
“…Passive distention of small pulmonary vessels at least partly accounts for the flow-mediated decrease in PVR, 91 which seems inconsistent with the notion of distention-mediated vasoconstriction. Storme and colleagues, 86 however, showed that, in the fetal lung, vasoconstriction with ductal compression occurs only when endothelial release of NO is blocked using NO synthase inhibition. They surmise that increased PA flow with ductal constriction causes endothelial release of NO, which prevents smooth muscle activation, but when NO production is inhibited, myogenic contraction is made manifest.…”
Section: Myogenic Vasoconstrictionmentioning
confidence: 99%
“…80 There is ample reason to think that myogenic constriction can also occur in the lung: first, stretch or increased intraluminal pressure stimulates constriction in segments of small PAs in vitro in multiple species, [81][82][83][84][85] and second, myogenic tone, at physiologically relevant pressures, has been demonstrated in the in situ lung of the ovine fetus 86,87 and (pace assertions that this response is lacking in normoxic mature animals 88 ) mature feline, canine, and ovine lungs. 42,89,90 An apparent objection to the pulmonary myogenic tone hypothesis is the observed effect of exercise on PVR (it generally decreases it).…”
Section: Myogenic Vasoconstrictionmentioning
confidence: 99%